2007
DOI: 10.1093/hmg/ddm238
|View full text |Cite
|
Sign up to set email alerts
|

Nesprin-1 and -2 are involved in the pathogenesis of Emery–Dreifuss muscular dystrophy and are critical for nuclear envelope integrity

Abstract: Emery-Dreifuss muscular dystrophy (EDMD) is a heterogeneous late-onset disease involving skeletal muscle wasting and heart defects caused, in a minority of cases, by mutations in either of two genes encoding the inner nuclear membrane (INM) proteins, emerin and lamins A/C. Nesprin-1 and -2 are multi-isomeric, spectrin-repeat proteins that bind both emerin and lamins A/C and form a network in muscle linking the nucleoskeleton to the INM, the outer nuclear membrane, membraneous organelles, the sarcomere and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
491
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 478 publications
(521 citation statements)
references
References 43 publications
25
491
2
3
Order By: Relevance
“…The latter increased in number with increasing passage number. The analysis of Nesprin-2 negative MEFs revealed that they had similar phenotypes as has been described previously for MEFs isolated from Nesprin-2 mouse mutants and for cells in which Nesprin-2 was depleted by shRNAs [15,20,23]. In particular, changes in the nuclear morphology and in cell migration resembled those that had been seen previously.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The latter increased in number with increasing passage number. The analysis of Nesprin-2 negative MEFs revealed that they had similar phenotypes as has been described previously for MEFs isolated from Nesprin-2 mouse mutants and for cells in which Nesprin-2 was depleted by shRNAs [15,20,23]. In particular, changes in the nuclear morphology and in cell migration resembled those that had been seen previously.…”
Section: Discussionsupporting
confidence: 77%
“…In human, mutations in the SYNE2 gene cause Emery-Dreifuss muscular dystrophy (EDMD) 5, an autosomal dominant disease[20]. Patients suffering from EDMD harbored a heterozygous DNA variation in the SYNE2 gene leading to a missense mutation pT89M in the C-terminal Nesprin-2β isoform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gene encodes a type-2 integral membrane protein located in the inner nuclear membrane, LAP1B. Because other proteins of the nuclear membrane such as laminA/C, emerin, nesprin-1 and nesprin-2 are known to cause muscular dystrophy phenotypes, TOR1AIP1 was selected as a possible novel nuclear envelopathy-related gene [14,15]. DNA sequencing of TOR1AIP1 from the genomic DNA of affected individuals IV:2, IV:5 and IV:7 showed that there was a homozygous G deletion at position c.186 (c.186delG) in the first exon of the gene, which was predicted to cause a frameshift leading to a premature stop codon ( Fig.…”
Section: Genetic and Molecular Studiesmentioning
confidence: 99%
“…This group of diseases known as nuclear envelopathies consist of a wide range of clinical syndromes, including muscular dystrophy, cardiomyopathy, lipodystrophy, mandibuloacral dysplasia, neuropathy, progeria, restrictive dermopathy, arthrogryposis, Pelger-Huet anomaly and leukodystrophy [14,15].…”
Section: Introductionmentioning
confidence: 99%